Host-Related Olfactory Behavior in a Fruit-Piercing Moth (Lepidoptera: Erebidae) in Far Eastern Russia. Issue 1 (20th June 2016) - Zaspel, Jennifer M.; Kononenko, Vladimir S.; Ignell, Rickard; Hill, Sharon R.
Abstract: The host preference of the economically important fruit piercing moth, Calyptra lata (Butler 1881), was studied when exposed to different fruits and the odors of those fruits in enclosed feeding assays and in a two-choice olfactometer. The fruits consisted of three ripe and locally available types: raspberries, cherries and plums. Moths were released in cages with the ripened fruit and observed for any feeding events, which were then documented. Moths fed on both raspberries and cherries, but not on plums. To test the role of olfactory cues in fruit preference, male moths were released singly in the two choice olfactometer, with one type of fruit odor released in one arm and background control air in the other. The behavior of the moths was recorded on video. Parameters scored were 1) time to take off, 2) flight duration and 3) total time to source contact. The moths showed a significant preference for raspberry odor, exhibited a neutral response to cherry odor and significantly avoided the odor of plums. These results indicate that Calyptra lata demonstrates selective polyphagic feeding behavior and uses olfactory cues from both preferred and non-preferred fruits to detect and locate potential food sources. The possible implications for pest control are discussed.